Air-assisted spraying and electrically charged droplets for Bemisia tabaci control in soybeans - Pelegrini, Gabriela [UNESP]; Souza, Antônio M [UNESP]; Ferreira, Pedro HU [UNESP]; Monteiro, Gabriel G [UNESP]; Ferreira, Marcelo C [UNESP] (Wiley, 2022)
BACKGROUND: The improvement of surface coverage and plant protection products deposition can be obtained by electrifying droplets, which are strongly attracted by plants, including the abaxial part of the leaves. Moreover, air assistance improves droplet penetration into the crop canopy, especially in the lower third of the plants. These technologies can help control soybean (Glycine max) whitefly, which preferentially lodges on the abaxial surface of the leaves. Thus, this study aimed to assess the effect of air-assisted spraying and electrically charged droplets to control whitefly in soybean, besides assessing surface coverage, plant protection product deposition, droplet size, and crop yield. RESULTS: Droplet electrification and air assistance did not change droplet size and uniformity classified as Fine. Surface coverage was not enhanced using air assistance and electrically charged droplets, where maximum coverage in the middle third of the plants was 4.55%. The results were not significant for spray plant protection products deposition. The number of nymphs per leaflet in the 2019/20 growing season was reduced with the used technologies, reducing from 10.9 to 3.0 nymphs per leaflet in the application with air-assisted and charged droplets, but not enough to differ from the untreated. On the other hand, the reduction was significant from the first assessment in the 2020/21 growing season. CONCLUSION: Air-assisted spraying plus electrically charged droplets, under the conditions of this experiment which corresponds to the application carried out in production areas, were not effective to affect whitefly control and soybean yield in comparison to the conventional application method. © 2022 Society of Chemical Industry.
Keywords: air assistance; electrifying droplets; Glycine max; whitefly